Sedimentation of Holocene tufa influenced by the Neolithic man: An example from the Sąspowska Valley (southern Poland). (12th May 2017) - Gradziński, Michał; Hercman, Helena; Rizzi, Małgorzata; Stachowicz-Rybka, Renata; Stworzewicz, Ewa
Abstract: A complex of inactive tufas, the thickness of which reaches 3.5 m, was studied in the lowermost segment of the Sąspowska Valley in the Kraków Upland (Ojców National Park, Poland). Five fluvial tufa barrages were recognized. They are composed of moss tufa and stromatolitic tufa accompanied with oncoidal rudstone and detrital tufa. Interbarrage ponded areas were filled with detrital tufa, lutite, and subordinately oncoidal rudstone, limestone gravel and peat-like deposit. Radiocarbon dates suggest that the tufa formed during Subboreal, Boreal and Atlantic time. The main difference between the tufa in the Sąspowska Valley and contemporaneous tufas in other valleys of the Kraków Upland is the higher amount of non-carbonate fraction in the former. Other Lower and Middle Holocene tufas of the Kraków Upland are composed mainly or exclusively of carbonate fraction. The non-carbonate fraction in fluviatile tufas in the Sąspowska Valley resulted from erosion of loess cover in the upper part of the catchment. The erosion was related to local activity of Neolithic flint miners who cleared forest at a local scale, dug shafts in loess cover and exploited flints from underlying weathered residuum of Jurassic limestone. Consequently, they made copious amounts of loose material available for transport down the valley and subsequent trapping within the tufa depositional system.